India's Undernourished Children : A Call for Reform and Action - Gragnolati, Michele; Shekar, Meera; Das Gupta, Monica; Bredenkamp, Caryn; Lee, Yi-Kyoung (World Bank, Washington, DC, 2013)
This paper explores the dimensions of child undernutrition in India, and examines the effectiveness of the Integrated Child Development Services (ICDS) program in addressing it. The paper finds that although levels of undernutrition in India declined modestly during the 1990s, the reductions lagged far behind that achieved by other countries with similar economic growth rates. Nutritional inequalities across different states, socioeconomic and demographic groups are large - and, in general, are increasing. The study also finds that the ICDS program appears to be well-designed and well-placed to address the multidimensional causes of malnutrition in India. However, there are several mismatches between the program's design and its actual implementation that prevent it from reaching its potential. The paper concludes with a discussion of a number of concrete actions that can be taken to bridge the gap between the policy intentions of ICDS and its actual implementation.